ANALISIS CELLO EXTENDED TECHNIQUES PADA KOMPOSISI MUSIK HNNOH III (2015) KARYA NURSALIM YADI ANUGERAH - Prastiawan, Ardy; Mering, Aloysius; Silaban, Christianly Yery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research based on the need of cello extended techniques literature in Indonesia that is not directly proportional to the existence of contemporary music works using this technique. The aims of this research are 1) the description of the simplest form of music composition Hnnoh III, 2) the description of musical notation of the cello extended techniques on the music composition Hnnoh III, 3) the description of how to play and the preparation to play the cello extended techniques on the music composition Hnnoh III. The method used in this research is a descriptive qualitative method and using musicology approach. The data contained in this study are the results of unstructured observation, interviews to expert informants namely Nursalim Yadi Anugerah who also a composer and cellist in the music composition Hnnoh III, document techniques and literature studies related to the cello extended techniques. The results of this study are the free form music on the music composition Hnnoh III and the cello extended techniques used include the Col Legno Tratto, Col Legno Tratto combined Tapping / Striking Left Hand, Very Fast Vibrato Harmonic, Doublestop Harmonic, Doublestop Clusters / Quarter Tones and Glissando Tremolo.Â Keywords:Â Music Composition Hnnoh III, Contemporary, Cello, Cello Extended Techniques.